Social enterprise housing supply chains for resource-constrained communities: a complexity lens approach - Boehme, Tillmann; Fan, Joshua; Birchnell, Thomas; Aitken, James; Turner, Neil; Deakins, Eric (Emerald, 2023)
Purpose: Delivering housing to resource-constrained communities is a complex process beset with difficulties. This study employs a complexity lens to examine the approach taken by a social enterprise in Australia to develop and manage a housebuilding supply chain for resource-constrained communities. Design/methodology/approach: The research team employed a longitudinal case study approach from 2017 – 2022, which utilised mixed methods to understand the phenomenon and gain an in-depth understanding of the complex issues and problem-solving undertaken by a social enterprise start-up. Findings: Balancing mission logic with commercial viability is challenging for a social enterprise. The supply chain solution that evolved accommodated the particulars of geography and the needs of many stakeholders, including the end-user community and government sponsors. Extensive and time-consuming socialisation and customisation led to a successful technical design and sustainable supply chain operation. Originality: This longitudinal case study contributes to knowledge by providing rich insights into the roles of social enterprises and how they develop and operate supply chains to fit with the needs of resource-constrained communities. Adding a contextual response dimension to an established complexity framework helped to explain how hybrid organisations balance commercial viability demands with social mission logic by amending traditional supply chain and governance practices. The case provides insights into supply chain configuration, needed changes, and potential impacts when a social enterprise as a focal actor inserts into a traditional for-profit construction supply chain. Practical implications: Analysing supply chain intricacies via a complexity framework is valuable for scholars and practitioners, assisting in designing and developing supply chain configurations and understanding their dynamics. Meeting the housing construction needs of resource-constrained communities requires the social enterprise to place societal focus at the centre of the supply chain rather than merely being a system output. The developed business model complements the engineering solution to empower a community-led housing construction supply chain.
Keywords: Supply chain complexity; construction; construction supply chain; social enterprise; resource-constrained communities